Descriptive Analysis of Nurses' Knowledge and Attitudes towards Nutritional Care in Oncology Settings": With a view to develop self-instructional module. (International Journal of Food and Nutritional Sciences, 2022)
Nutritional care is crucial in oncology, significantly affecting patient outcomes and quality of life. Despite its importance, many nurses lack sufficient training and confidence in providing nutritional support. Understanding nurses' knowledge and attitudes towards nutritional care is essential to identify educational needs and improve patient care in oncology settings.